Is model of care associated with infant birth outcomes among vulnerable women? A scoping review of midwifery-led versus physician-led care - Daphne N. McRae; Nazeem Muhajarine; Kathrin Stoll; Maureen Mayhew; Saraswathi Vedam; Deborah Mpofu; Patricia A. Janssen (Elsevier, 2016)
This scoping review investigates if, over the last 25 years in high resource countries, midwives' patients of low socioeconomic position (SEP) were at more or less risk of adverse infant birth outcomes compared to physicians' patients. Reviewers identified 917 records in a search of 12 databases, grey literature, and citation lists. Thirty-one full documents were assessed and nine studies met inclusion criteria. Eight studies were assessed as moderate in quality; one study was given a weak rating. Of the moderate quality studies, the majority found no statistical difference in outcomes according to model of care for preterm birth, low or very low birth weight, or NICU admission. No study reported a statistically significant difference for small for gestational age birth (2 studies), or mean or low Apgar score (4 studies). However, one study found a reduced risk of preterm birth (AOR=0.70, p<0.01), and heavier mean infant birth weight (3325 g vs. 3282 g, p<0.01) for midwifery patients. Another study reported lower risk of low (RR=0.59, 95% CI: 0.46, 0.73) and very low birthweight (RR=0.44, 95% CI: 0.23, 0.85) for midwifery care. And, a third study reported a decrease in stays (1-3 days) in NICU (Adjusted Risk Difference=−1.8, 95% CI: −3.9, 0.2) for midwifery patients, though no overall difference in NICU admission of any duration. Other studies reported significant differences favoring midwifery care for mean birth weight (3598 g vs. 3407.3 g, p<0.05; 3233 g vs. 3089 g, p<0.05; 2 studies) and very low birth weight (OR=0.35, 95% CI:0.1, 0.9), for sub-groups within the larger study populations. This scoping review documented heterogeneity in study designs and analytical methods, inconsistent findings, moderate methodological quality, and lack of currency. There is a need for new studies to definitively establish if and how a midwifery-led model of care influences birth outcomes for women of low SEP. Keywords: Midwifery, Socioeconomic position, Vulnerable women, Prenatal care, Infant birth outcome, Preterm birth